State and Local Governance in Nigeria - World Bank (Washington, DC, 2013)
The purpose of this study is to increase knowledge about state capacity in Nigeria by taking stock of governance issues, including public financial management and civil services, and analyzing them in representative states across the regions, as states assume an expanded role in delivering services to their populations under the 1999 constitution. Specifically, the study lays the groundwork for preparing a program of assistance to state governments, should the Federal Government seek financing from the Bank. Before capacity can be strengthened, the context for capacity building must be understood and the constraints analyzed. Thus the study focuses both on the evolving story of federalism in Nigeria, as well as the challenges states face in managing their finances and delivering services in the aftermath of misrule and decay under the military. Six states were selected for review: Bauchi, Nasarawa, Rivers, Anambra, Ogun and Sokoto--one from each of the geo-political zones of Nigeria. These are some of the principal findings: There is a great deal of variation across states in their capacity for governance. A new generation of state governors is emerging, albeit still a minority. Some are beginning to address public sector reform, through civil service modernization and right sizing, and strengthening financial management. These last are suggested areas for support, but they must be calibrated with the commitment to state reform, and not provided as an entitlement.